2012
DOI: 10.1017/s0007114512003601
|View full text |Cite
|
Sign up to set email alerts
|

Hydration biomarkers in free-living adults with different levels of habitual fluid consumption

Abstract: Little is known about the impact of habitual fluid intake on physiology. Specifically, biomarkers of hydration status and body water regulation have not been adequately explored in adults who consume different fluid volumes in everyday conditions, without prolonged exercise or environmental exposure. The purpose of the present study was to compare adults with habitually different fluid intakes with respect to biomarkers implicated in the assessment of hydration status, the regulation of total body water and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

20
213
1
5

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 172 publications
(244 citation statements)
references
References 30 publications
20
213
1
5
Order By: Relevance
“…Total water intake (sum of water from food moisture and fluids) varies considerably in the common population [8, 9]. The impact of low daily water intake on long term health has, in the past, attracted little attention [10].…”
Section: Impact Of Drinking Behaviour On the Vasopressin-cortisol-sgkmentioning
confidence: 99%
See 2 more Smart Citations
“…Total water intake (sum of water from food moisture and fluids) varies considerably in the common population [8, 9]. The impact of low daily water intake on long term health has, in the past, attracted little attention [10].…”
Section: Impact Of Drinking Behaviour On the Vasopressin-cortisol-sgkmentioning
confidence: 99%
“…A recent study revealed, however, that plasma vasopressin (ADH) levels were significantly enhanced in low drinkers (≤ 1.2 litres/d of total fluid intake, i.e. sum of drinking water and any other fluids) as compared to high drinkers (2–4 litres/d) [8, 11]. Vasopressin is a known powerful stimulator of glucocorticoid release [4, 5] and low drinkers had indeed significantly higher plasma cortisol levels [8].…”
Section: Impact Of Drinking Behaviour On the Vasopressin-cortisol-sgkmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, although a review of international studies found significant differences in hydration status by age, gender, race/ethnicity, and culture, 11 there is limited evidence about the population distribution of urine osmolality and inadequate hydration among US children, particularly whether disparities in hydration status exist across population groups defined by race/ethnicity, household income, gender, or age. Although small, laboratory-based studies of adults suggest that higher beverage intake is associated with better hydration status (regardless of beverage type), 12,13 preliminary evidence has suggested that plain water may be associated with better hydration status in children. 10 Given that little is known about how consumption of different beverages may affect population hydration status in children, the potential solutions to reducing inadequate hydration are unclear.…”
mentioning
confidence: 99%
“…Moreover, individuals with habitually lower fluid intake have higher circulating AVP, lower 24-hour urine volume and higher urine concentration [10,11] . Given that higher circulating AVP is an indicator of chronic or habitual antidiuresis (indicating insufficient water intake), these findings suggest that there may be biologically significant interconnections between AVP, water intake and renal and metabolic health ( fig.…”
Section: Introductionmentioning
confidence: 99%